Assessment of wind energy potential mapping for Peninsular Malaysia / Mohammad Rafiqul Islam - Mohammad Rafiqul, Islam (2011)
Wind energy generation is growing rapidly worldwide and will continue to do so for the foreseeable future. In this study, the most accepted 2-parameter Weibull distribution model has been applied for assessment of wind energy potentiality. The wind directions have been also identified using the WRPLOT View software. The Geographical Information System (GIS), ArcGIS 9.3 software, has been applied to present the predicted monthly and yearly mean wind speed in the form of contour maps. The wind speed data of 15 stations has been collected from the Malaysian Meteorological Department over the period of 2008-2009. Based on the experimental data, it is found that the numerical values of both Weibull parameters (k and c) for Peninsular Malaysia vary over a wide range. It is found that the daytime, from 8 am to 6 pm, is windy for all the years, while the night time is relatively calm. Most of the monthly mean wind speed values are between 1.5 m/s to 4.5 m/s, but some are over 4.5 m/s and few are under 1.5 m/s. The mean wind speeds for all the years are lower than 4.5 m/s and the range of the yearly mean wind speed values is from 0.90 to 4.06 m/s. It is found that the yearly mean wind speed at Mersing is 4.06 m/s in 2008 and 4.01 m/s in 2009, which is capable of producing commercial wind energy by using current technology. The monthly highest value of wind power density was found to be 227.1 W/m2 at Mersing in January, 2009 and the lowest value of wind power density was 1.3 W/m2 in November 2008 at Batu Embun. The average value of the monthly wind power density was estimated 26.76 W/m2. The range of the values of monthly wind energy density was found to be between 11.23 to 1962 kWh/m2/year whereas the average wind energy density was found to be 231.20 kWh/m2/year. Mersing is the most „windy‟ place with the largest scale parameter c, and its most frequent wind speed is 3.5 m/s. The maximum percentage of error between Weibull and observed wind speed frequencies occur at 3 m/s or more than 3 m/s is around 20%. From cumulative distribution function, it is found that Mersing will have the highest operating possibility of 67% (around 5789 hours per year). For all the sites, the prevailing winds from the most probable wind directions on the percentage ranging from 15 to 41% and the wind speeds less than 3 m/s are ranging from 11.2-89.2%. The geographical parameters (latitude, longitude, and altitude), and months of the year were used as input data, while the monthly and yearly mean wind speeds were found as the output. It is seen that the southern part of Peninsular Malaysia is windier than that of the other parts in Peninsular Malaysia. The predicted wind speed values are given in the form of monthly and yearly maps, which can be easily used for assessment of wind energy potential for different locations within Peninsular Malaysia.